2022
DOI: 10.1111/ene.15422
|View full text |Cite
|
Sign up to set email alerts
|

Disability progression in multiple sclerosis patients using early first‐line treatments

Abstract: Background and purpose: Therapeutic management of relapsing-remitting multiple sclerosis (RRMS) has evolved towards early treatment. The objective was to assess the impact of early treatment initiation on disability progression amongst RRMS first-line-treated patients. Methods: This study included all incident RRMS cases starting interferon or glatiramer acetate for the first time from 1 January 1996 to 31 December 2012 (N = 5279) from 10 MS expert Observatoire Français de la Sclérose en Plaques centres. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Second, time to treatment initiation is accounted for at the time of disease onset instead of at MS diagnosis. 12,[18][19][20]22,24 This is important because in this study, the included classical MS covariates are collected when the clinical disease starts and not in a time frame in which the disease might evolve or progress. 40,41 Other important difference is that in our cohort, patients are allowed to enter on risk of disability before the MS diagnosis, as long as treatment is initiated between the first demyelinating event and MS diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, time to treatment initiation is accounted for at the time of disease onset instead of at MS diagnosis. 12,[18][19][20]22,24 This is important because in this study, the included classical MS covariates are collected when the clinical disease starts and not in a time frame in which the disease might evolve or progress. 40,41 Other important difference is that in our cohort, patients are allowed to enter on risk of disability before the MS diagnosis, as long as treatment is initiated between the first demyelinating event and MS diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…12,[18][19][20][21][22][23] Despite the effectiveness displayed by real-world studies on decreasing risk of disability, it is important to underline some methodological shortcomings influencing results. 12,[18][19][20][21][22][23][24] In multicentric studies, data are usually collected following different protocols, which makes such information difficult to harmonize under a common database. For instance, differences in inclusion criteria, clinical visit frequency, scales to measure disability, or the use of predetermined variables among centers may add inconsistency when gathering information within the same platform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected an EDSS score of 3.0 as the initial disability milestone because it signifies the beginning of mild to moderate irreversible disability. Additionally, an EDSS score of 6.0 was chosen as the subsequent milestone because it marks the first sign of dependence on ambulatory assistance [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“… 1 , 2 The initiation of treatment with a disease-modifying therapy (DMT) at the time of first presentation of symptoms consistent with or suggestive of MS provides benefits over delaying treatment. 3 8 Long-term follow-up of patients from randomized trials has shown a greater benefit for patients originally assigned to treatment groups as opposed to those originally assigned to placebo groups. 9 14 …”
Section: Introductionmentioning
confidence: 99%